Relevansi dan Tantangan Bangunan Pemikiran Kritis dan Pemecahan Masalah Pendidikan Islam dalam Mengembangkan Literasi Informasi dan Kesadaran global Abad 21 - Salim Ashar (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2019)
Throughout written history, starting from the plateau with its republic, critical thinking and problem solving are considered to be a 3rd century BC skill, today with technological advances marked by Artificial intelligence it still considers it to be 21st Century thinking or the main thought of the revolution Industry 4.0. the assumption that the emergence of digital technology requires fundamental changes to the curriculum and to the teaching and learning approach to educating